KOMPENSASI DI CV. GEO KARYA PRATAMA - Andi Ronaldi (LPPM Institut Pendidikan Nusantara Global, 2023)
Compensation is a form of payment given by the company to employees in return for the contributions and achievements that have been given. In the world of work, compensation is one of the important factors to motivate employees to perform well. Therefore, companies must design a compensation system that is in accordance with the performance and contribution of employees. CV. Geo Karya Pratama is a company engaged in Topography Survey and Land Investigation, where the compensation system provided by this company is important to be studied. The purpose of this study is to determine the compensation system applied by CV. Geo Karya Pratama, as well as the impact of the compensation system on company employees. The method used in this research is qualitative research with a case study approach. Data was obtained through interviews with company employees and CV management. Geo Karya Pratama. Data analysis was conducted using the content analysis method. The results showed that CV. Geo Karya Pratama implements a compensation system that is quite varied and flexible. The compensation system consists of several components, namely basic salary, health allowance, attendance allowance, and meal allowance. The company's employees are satisfied with the compensation system implemented and feel that the system is quite fair. The impact of the compensation system implemented by CV. Geo Karya Pratama on the company's employees is the increased motivation and work performance of employees.